2021
DOI: 10.1093/milmed/usab361
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Sensors Detect Movement Differences in the Portable Warrior Test of Tactical Agility After mTBI in Service Members

Abstract: Introduction Assessment of functional recovery of service members following a concussion is central to their return to duty. Practical military-relevant performance-based tests are needed for identifying those who might need specialized rehabilitation, for evaluating the progress of recovery, and for making return-to-duty determinations. One such recently developed test is the ‘Portable Warrior Test of Tactical Agility’ (POWAR-TOTAL) assessment designed for use following concussion in an acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Analyses will be performed on the time-series of tri-axial readings of the sensor’s accelerometer and gyroscope, sampled continuously at 100Hz during the task execution. Our previous POWAR-TOTAL study 16 found that rapid transitional movements of lowering from running to prone position and of performing combat rolls were significantly more sensitive to mTBI than running. For example, according to our Receiver Operating Characteristic (ROC) curve analysis, SMs recovering from concussion are more accurately discriminated from their concussion-free peers based on the duration of the transitional movements (area under the curve AUC = 0.83) than on the duration of the entire task (AUC = 0.71).…”
Section: Data Processingmentioning
confidence: 92%
See 3 more Smart Citations
“…Analyses will be performed on the time-series of tri-axial readings of the sensor’s accelerometer and gyroscope, sampled continuously at 100Hz during the task execution. Our previous POWAR-TOTAL study 16 found that rapid transitional movements of lowering from running to prone position and of performing combat rolls were significantly more sensitive to mTBI than running. For example, according to our Receiver Operating Characteristic (ROC) curve analysis, SMs recovering from concussion are more accurately discriminated from their concussion-free peers based on the duration of the transitional movements (area under the curve AUC = 0.83) than on the duration of the entire task (AUC = 0.71).…”
Section: Data Processingmentioning
confidence: 92%
“…To measure precisely the duration of lowering the body from the vertical to prone position and the duration of combat rolls, we will adopt the same machine-learning approach we used in the POWAR-TOTAL study, which involves training Radial Basis Function (RBF) networks on the accelerometer and gyroscope data recorded during run/roll activities 16 .…”
Section: Inertial Sensor Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a single training and testing method for agility qualities in previous related studies, and there is a lack of studies that combining functional training and badminton agility qualities [12][13][14]. The portable device studied by Favorov, Oleg, can detect the movement time of prescribed movements well, but it lacks the most important randomness factor in agility training [15]; this is not the same as the agile training instrument studied in this paper, which can continuously train and improve the reaction ability of athletes by randomly starting the lower computer. Dieujuste can better study the changes in the blood oxygen of athletes during exercise by wearing portable devices [16].…”
Section: Introductionmentioning
confidence: 99%